SOCRATIC QUESTIONING TO PROMOTE EFL STUDENTS’ CRITICAL THINKING IN A LANGUAGE LEARNING - Suhardiana, I Putu Andre (Yavana Bhasha : Journal of English Language Education, 2019)
This paper addressed the use of the Socratic Questioning method as an attempt to promote EFL students' critical thinking in language learning. It is ordinarily understood that the process of learning the language tends to focus more on how to answer questions rather than how to ask productive, systematic, and directed questions. Questioning as a means to fulfil curiosity is a driving factor for critical thinking activities. Questioning is able to direct the task and define the problem so that it will spur and trigger students' critical thinking. The use of Socratic Questioning and critical thinking methods embraces and encourages the analysis of Bloom's taxonomy integrally since Bloom's critical thinking is assigned as one of the highest levels of thinking in cognitive domains. Socratic Questioning, critical thinking, and Bloom's taxonomy are lines that must be passed in a language learning process in order to achieve the quality of skills which surely depends on the quality of thinking.